2022
DOI: 10.1161/strokeaha.120.034019
|View full text |Cite
|
Sign up to set email alerts
|

Posterior National Institutes of Health Stroke Scale Improves Prognostic Accuracy in Posterior Circulation Stroke

Abstract: Background and Purpose: The National Institutes of Health Stroke Scale (NIHSS) underestimates clinical severity in posterior circulation stroke and patients presenting with low NIHSS may be considered ineligible for reperfusion therapies. This study aimed to develop a modified version of the NIHSS, the Posterior NIHSS (POST-NIHSS), to improve NIHSS prognostic accuracy for posterior circulation stroke patients with mild-moderate symptoms. Methods: Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 29 publications
1
37
0
5
Order By: Relevance
“…Our findings also reveal associations between admission NIHSS, pc-ASPECTS, and recanalization and favorable outcomes at 90 days, which is further supported by previous studies [ 30 , 31 ]. Interestingly, we found sex as an independent predictor of mortality within 90 days for young patients.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings also reveal associations between admission NIHSS, pc-ASPECTS, and recanalization and favorable outcomes at 90 days, which is further supported by previous studies [ 30 , 31 ]. Interestingly, we found sex as an independent predictor of mortality within 90 days for young patients.…”
Section: Discussionsupporting
confidence: 91%
“…Management of patients with mild symptoms is challenging as some may improve without EVT while others may deteriorate. The NIHSS also has reduced sensitivity to detect potentially disabling deficits in patients with posterior circulation stroke [ 35 ]. Prior studies showed divergent results of EVT in these patients as it carries increased procedural risks, especially in patients with underlying intracranial atherosclerotic disease (ICAD) [ 12 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NIHSS also has reduced sensitivity to detect potentially disabling deficits in patients with posterior circulation stroke. 35 Prior studies showed divergent results of EVT in these patients as it carries increased procedural risks, especially in patients with underlying intracranial atherosclerotic disease (ICAD). 12,36,37 Randomized trials comparing EVT versus MM in BAO patients with mild strokes are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A median NIHSS score of one, and average of 2, in imaging confirmed stroke patients in our cohort suggests that further work is needed to develop scoring systems appropriately weighted for posterior circulation strokes. Perhaps the addition of gait and truncal ataxia would improve the prognostic accuracy and hence the therapeutic value of NIHSS scores in patients with posterior circulation strokes with mild to moderate symptoms [22].…”
Section: Discussionmentioning
confidence: 99%